Non-traumatic anterior mediastinal abscess in childhood - Sandeep Kumar; Virendra Kumar; Amit Bishnoi; Rajiv Chadha (Wolters Kluwer Medknow Publications, 2011)
Anterior mediastinal abscesses (MAs) due to a non-traumatic etiology are extremely rare in childhood and only 13 such cases have been reported in the literature. We report a 5-year-old male child with disseminated staphylococcal infection and a large non-traumatic anterior MA, who had a successful recovery after surgical drainage of the abscess.